The mechanisms linking work-life balance and well-being among Chinese college teachers - Wei, Changwu; Ma, Yan; Ye, Jian-Hong (Frontiers in Public Health, 2025)
IntroductionCollege faculty well-being is crucial for higher education goals and sustainability. However, their well-being is lower than in other professions. High job demands in academia impede work-life balance, a key well-being determinant, while work engagement can counterbalance these demands. However, the mechanisms linking job demands, work engagement, work-life balance, and well-being remain underexplored.MethodsThis study explores these mechanisms using the Work-Life Balance model. Semi-structured interviews were conducted with 13 Chinese college teachers, and thematic analysis was used to identify themes and construct a systematic model.ResultsPerceived job value, family support, and financial security can reduce job demands and enhance work-life balance. Excessive demands, however, may overwhelm teachers, causing health issues and disrupting personal life. Job value, responsibility, work interest, and family support also boost work engagement, which, combined with rewards, improves balance. Financial security, family support, and social status are critical for achieving work-life balance, which is essential for health, interpersonal harmony, and overall well-being.DiscussionThese findings reveal complex, non-linear relationships among job demands, work engagement, work-life balance, and well-being in Chinese higher education. They highlight the need for nuanced understanding and provide insights for policy and institutional reforms.